In and out of the crisis − Greece - Fekete, Klára (Acta Agraria Debreceniensis, 2014)
Facing an unprecedented crisis, both Greece and the international actors have been struggling to facilitate a solution that assures sustainable growth through restructuring the economy and the national accounts. However, enduring solutions cannot be born but through a very thorough understanding of the root causes and the nature of the problem. A country far from fully exhausting her resources is also experiencing increasing tension in the society. Highlighting some key characteristics of the most relevant parties, the factors undermining the society and the real growth potential of the country will be addressed and challenged with key economic principles. This cross-sectional study aims to pave way to a more comprehensive approach to prevent any disagreements or delays that was experienced in late 2013. The findings refer to the assets of the country and identify some basic requirements to boosting the Greek economy. The lessons learned and the growth potential of the country is being discussed in the concluding remarks, pointing to some factors to be considered in the future.